Proportional-resonant controlled NPC converter for more-electric-aircraft starter-generator - Dehghani Tafti, Hossein (2015)
More electric aircraft (MEA) technology is achieved by exchanging various mechanical and pneumatic elements of a conventional aircraft with their equivalent electrical devices in order to increase the reliability and decrease the maintenance. This paper proposes a proportional resonant (PR) controller together with the adaptive space vector modulation (ASVM) technique for the more electric aircraft (MEA) starter-generator neutral-point clamped (NPC) converter. The proposed controller is implemented in the stationary (αβ) frame where the calculated reference voltages of the PR controller can be directly fed into the ASVM. Hence, the main objectives of the proposed controller are to reduce the computational complexity and the steady state error by decreasing the required number of framework transformations units. On top of that, the ASVM technique provides a proper DC-link capacitor voltage balancing with improved output power quality. The dynamic performance of the proposed controller is evaluated under both initial starting interval and generating mode.